Impact of Renewable Based Microgrid Supply/Demand Profiles on Low Voltage Distribution Networks. (December 2016) - Zehir, M.A.; Batman, A.; Sonmez, M.A.; Font, A.; Tsiamitros, D.; Stimoniaris, D.; Kollatou, T.; Bagriyanik, M.; Ozdemir, A.; Dialynas, E.
Abstract: Integration of distributed generation (DG) from renewables into power systems has been one of the major challenges for operators. Impact of bidirectional power flow on the bus voltages and on the power losses is more severe in low voltage networks, due to high R/X ratio of the lines. Operators generally evaluate capacity additions considering the extreme cases. However, extreme cases occur rarely in a long-term operation or their impact is generally less than expected. This study presents daily operation analysis of a low voltage network including a renewable supported microgrid. Using a field-data based virtual test bed, daily variations in DG output power, residential demand and network voltages are simulated. The analysis reveals the occurrence rate of extreme cases in daily operation and changes in the line losses of low voltage networks with microgrids.